Rupture of an aortic aneurysm into the pulmonary artery. An unusual case with antemortem diagnosis. - Blumenthal, J (1970)
An acquired aorta-to-pulmonary artery shunt from rupture of a thoracic aortic aneurysm in an elderly patient is reported. The diagnosis was suspected clinically and was confirmed by special cardiac studies. Surgical intervention was refused by the patient who died shortly after admission to the hospital.